Level of ultrasonic energy to study aggregate stability of a Latosol (Oxisol) under different uses - de Sá, Marcos Aurélio Carolino; de Lima, José Maria; de Mello, Carlos Rogério (Pesquisa Agropecuaria Brasileira, 2002)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objective of this work was to identify the level of ultrasonic energy that better detect differences in the aggregate stability influenced by soil use. Three replicated samples of aggregates < 2 mm of a Dusky Red Latosol from Lavras, MG, Brazil, were collected under different uses: coffee plantation (two and 13 years), annual crops (30 years), pasture (26 years), Pinus sp. and Eucaliptus sp. (both 27 years), and native forest. Ultrasonic energy at 0.0, 3.0, 9.1, 18.1, 36.3, 72.5, 108.8, 145.1 and 181.4 J mL-1 were applied in each sample. Better sensibility and smaller coefficients of variation were observed between 30 to 90 J mL-1, but the best energy level was 36.3 J mL-1, which has provided aggregate stability decreases in the following order: forest, Eucaliptus sp. and Pinus sp., pasture and 13 years coffee plantation, annual cultures, two years coffee plantation. Dispersion indexes increase with the decrease of the organic carbon (r between -0.60** and -0.83**), confirming the importance of the soil use in aggregate stability.